Effects of fructose and glucose overfeeding on hepatic insulin sensitivity and intrahepatic lipids in healthy humans12. (25th May 2013) - Lecoultre, V.; Egli, L.; Carrel, G.; Theytaz, F.; Kreis, R.; Schneiter, P.; Boss, A.; Zwygart, K.; Lê, K‐A.; Bortolotti, M.; Boesch, C.; Tappy, L.
Abstract: Objective: To assess how intrahepatic fat and insulin resistance relate to daily fructose and energy intake during short‐term overfeeding in healthy subjects. Design and methods: The analysis of the data collected in several studies in which fasting hepatic glucose production (HGP), hepatic insulin sensitivity index (HISI), and intrahepatocellular lipids (IHCL) had been measured after both 6‐7 days on a weight‐maintenance diet (control, C; n = 55) and 6‐7 days of overfeeding with 1.5 (F1.5, n = 7), 3 (F3, n = 17), or 4 g fructose/kg/day (F4, n = 10), with 3 g glucose/kg/day (G3, n = 11), or with 30% excess energy as saturated fat (fat30%, n = 10). Results: F3, F4, G3, and fat30% all significantly increased IHCL, respectively by 113 ± 86, 102 ± 115, 59 ± 92, and 90 ± 74% as compared to C (all P < 0.05). F4 and G3 increased HGP by 16 ± 10 and 8 ± 11% (both P < 0.05), and F3 and F4 significantly decreased HISI by 20 ± 22 and 19 ± 14% (both P < 0.01). In contrast, there was no significant effect of fat30% on HGP or HISI. Conclusions: Short‐term overfeeding with fructose or glucose decreases hepatic insulin sensitivity and increases hepatic fat content. This indicates short‐term regulation of hepatic glucose metabolism by simple carbohydrates.